ASOSIASI JAMUR MIKORIZA ARBUSKULA DENGAN PEREPAT (Combretocarpus rotundatus Miq) DAN JELUTUNG (Dyera lowii Hook) DI LAHAN GAMBUT - , Burhanuddin, Ir.,MP.; , Prof. Dr. Ir. Siti Kabirun ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In 1995 has made the opening of peatland in Central Kalimantan, known as the One Million Hectare or Mega Rice Project that the total area 1.4571 million hectares. Land clearing is accompanied by making the canal. As a result of making the canal with a total length of 2,008.7 km with a variety of widths and depths, there has been damage to the hydrological status of the region that is happening drastically very excessive and low water retention and water table (Limin et al., 2008). Moving from the fact mentioned above, it is deemed very important to be repaired through a conservation effort that is by doing a recovery on peat soil with human intervention. However, this recovery activities will always be faced with problems caused by land clearing peatland include: (1) ground water surface shrank, (2) drought, (3) pH of acid soil, (4) and nutrient poor (5 ) low microorganism activity. Effort to overcome these constraints, it should be an appropriate alternative technology that is with biofertilizer. The research goal are to find and identify endemic species Arbuscular Mycorrhizal Fungi (AMF) in peat soil Ex-PLG block C Kalampangan Central Kalimantan Province, to find the AMF species which effective to increase the seedling growth of perepat and jelutung, to know the dosage of phosphate (P) fertilizers using SP 36 and phosphate rock to increase the seedling growth of perepat and jelutung which inoculated with AMF and also to study the effect of water table, P fertilizers and inoculation of AMF to growth of perepat and jelutung. The field research to explore isolate source were done at the Million Hectare Peatland Blok C Kalampangan Central Kalimantan Province. A series of seedling research were done at green house laboratory of soil science Agriculture Faculty of Gadjah Mada University. The research were provided from April 2006 until August 2009. The seed of perepat and jelutung were collected from natural stand from peatland Ex-PLG block C Kalampangan. The seedling research used randomized factorial design with three replication. The observation was done at seedling of perepat and jelutung had age 4 weeks, 8 weeks, and 14 weeks after weaning. The observation including the measurement of height, diameter, number of leaf and dry weight of shoot, the plant absorption of P, the infection of root, the observation were done after harvesting. From the whole peatland Ex- PLG at block C Kalampangan that has been investigaed, there has 12 species AMF that is including in 3 genera of AMF that are Glomus (7 species), Gigaspora (2 species), and Acaulospora (2 species). There are five species of AMF that are endemic of peatland that were successfully isolated and reproduced that are Glomus sp 1, Glomus sp 2, Glomus sp 3, Glomus sp 4, and Gigaspora sp 1 from those 11 species. The measurement of parameters such is height, diameter, number of leaf, dry weight of shoot and the absorption of P of plant in the trial research of 5 species of AMF isolate could increase the growth of perepat and jelutung seedling. One of AMF species that effective to increase the growth of perepat and jelutung seedling is Glomus sp 3. At the trial research of SP 36 fertilizer dosage to perepat and jelutung seedling that had been inoculated with Glomus sp 3 proven that 100 ppm dosage of the fertilizer is the best dosage and followed by 125 ppm dosage stimulated the growth of perepat and jelutung seedling. At the trial research of phosphate rock fertilizer dosage to perepat and jelutung seedling that had been inoculated with Glomus sp 3 proven that 100 ppm dosage is the best to stimulated the growth of those two seedling. At the trial research of water table of perepat and jelutung seedling that had been fertilized with SP 36 100 ppm dosage and inoculated with Glomus sp 3 proven that the best water table is 20 cm and followed 30 cm. At the trial research of perepat and jelutung seedling water table which fertilized with phosphate rock with 100 ppm dosage and inoculated with Glomus sp 3 proven water table 20 cm is the best, and followed by water table 30 cm for perepat seedling. For jelutung seedling, the best water table respectively is 20 cm, 10 cm, and 1 cm flooded. From the research it can be conclude that Glomus sp 3 that had been combine with P fertilizer with 100 ppm dosage and planted at water table 20 cm, and 10 cm can be used widely to increase the growth of perepat (C. rotundatus Miq) and jelutung (D. lowii Hook) seedling at nursery.